Toward Solutions for Youth Employment : A 2015 Baseline Report--Overview - World Bank Group (World Bank, Washington, DC, 2015)
Solutions for Youth Employment (S4YE) were launched in October 2014 as a multi-stakeholder coalition to positively disrupt the youth employment landscape. S4YE is a partnership initiated by the World Bank, Plan International, the International Youth Foundation (IYF), and Youth Business International (YBI), RAND, Accenture, and the International Labor Organization (ILO) with a view to contributing to a world where all youth have access to work opportunities. The mission of S4YE is to provide leadership and catalytic action and mobilize efforts to significantly increase the number of young people engaged in productive work by 2030. It seeks to develop innovative solutions through practical research and active engagement with public, private and civil stakeholders, to enable solutions for all youth at scale. This inaugural report explores how S4YE can find and advance solutions to the challenges of getting all youth into productive work.